Cationic Nanomaterials for Autoimmune Diseases Therapy - Xie, Baozhao; Du, Keqian; Huang, Fujian; Lin, Zhiming; Wu, Linping (Frontiers in Pharmacology, 2022)
Cationic nanomaterials are defined as nanoscale structures smaller than 100 nm bearing positive charges. They have been investigated to apply to many aspects including clinical diagnosis, gene delivery, drug delivery, and tissue engineer for years. Recently, a novel concept has been made to use cationic nanomaterials as cell-free nucleic acid scavengers and inhibits the inflammatory responses in autoimmune diseases. Here, we highlighted different types of cationic materials which have the potential for autoimmune disease treatment and reviewed the strategy for autoimmune diseases therapy based on cationic nanoparticles. This review will also demonstrate the challenges that are encountered during the development of cationic materials-based therapeutics for autoimmune diseases and possible solutions.